Strategic Planning in an Effort to Improve Service Quality at Wakatobi Regional General Hospital using Service Quality - Usamah Usamah; Tongam Sirait; Mentiana Sibarani; Ronny Samsul Bahri (Riviera Publishing, 2024)
The quality of health services in hospitals is an important aspect that affects patient satisfaction and health outcomes. At RSUD Wakatobi, evaluation of service quality is important to ensure that the services provided are in accordance with patient expectations and applicable standards. This study aims to analyze the quality of service at RSUD Wakatobi based on these dimensions, focusing on the application and effectiveness of each dimension in the context of health services at the hospital. This research uses descriptive qualitative research with inductive data analysis and uses research informants consisting of functional officials in charge of providing services at RSUD Wakatobi and administrative staff of RSUD Wakatobi as primary data sources. The data analysis technique used by researchers is descriptive data analysis, with the results showing that, based on the results of the above research, in this case the services applied at the Wakatobi Regional General Hospital are still not in accordance with the dimensions of service quality where physical evidence. While those that have been applied include reliability, assurance, empathy, and responsiveness. Service quality needs to be applied by every public service in providing services to patients because one of the good service qualities is the comparison between reality and expectations of patients of the Wakatobi Regional General Hospital. The implication of this research is the importance of developing and implementing improvement strategies in the physical evidence dimension to improve service quality at Wakatobi Regional General Hospital.